HUBUNGAN ANTARA KEBIASAAN BELAJAR, FASILITAS BELAJAR DAN PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI SE-KECAMATAN PAJANGAN - Ardika Agus Tirani (Universitas Sarjanawiyata Tamansiswa, 2017)
Descriptively, the purpose of this study is to know the tendency of the custom study, facility study and parents’ attention and the achievement Math of the students of VII of Junior High School Negeri in Pajangan district on 2013/2014 academic year. Correlatively, the purpose is to determine the relationship between custom study, study facility and parents’ attention and the achievement Mathematics of the students of VII of Junior High School Negeri in Pajangan district on 2013/2014 academic year. This action research is descriptive correlation like ex post facto. The population of this study was all students of VII in Pajangan district on 2013/2014 academic year. The sampling technique used was simple random sampling. The result of research shows descriptively that it has tendency to the advanced custom study on the average as big as 67,06, 65,70 on the study facility, parents’ attention as big as 66,83, and the mathematics study achievement is amount to 15,97. While it shows correlatively that there is a positive context and significance among the custom study, study facility, and parents’ attention togetherness with the achievement mathematics. With the value correlation (R) between X1,X2 and X3 as big as 0,865 and efficient of decision 0,748.